A priest coping with a new place : a vocational psychology and trauma reading of Ezekiel's priestly identity - Meyer, Esias E. (University of Pretoria, 2023)
Thesis (PhD (Old Testament and Hebrew Scriptures))--University of Pretoria, 2023.